GEOLOGI DAN PENGARUH INTRUSI TERHADAP KUALITAS BATUBARA SEAM A1 DAN A2 FORMASI MUARA ENIM DAERAH TAMBANG AIR LAYA, KECAMATAN LAWANG KIDUL, KABUPATEN MUARA ENIM, PROVINSI SUMATERA SELATAN - Adhimas Permana Putra (Jurnal Ilmiah Geologi PANGEA, 2016)
ABSTRACT - Intrusion is one of reasons that caused difference of coal rank. Changes in coal rank due to by pressureand temperature which occurs in particular time and pressure by intrusion. In order to determine coal rank, which canbe done by Proximate Analyzing (Chemistry Test, ASTM). Which determines percentage of moisture, volatile matter,fixed carbon, and ash with a certain method at general coal laboratory? Effect of intrusion in coal ranks not tooextensive, it only affects the area that has direct contact to the intrusion. The closer the coal to the intrusion, the morepossibility of better rank than the coal that further to the intrusion.Keywords: intrusion, coal rank.